CSR, corporate reputation and financial performance of Islamic banks in Malaysia: Stakeholders’ perceptions / Fatimah Noor Rashidah Mohd Sofian - Fatimah Noor Rashidah , Mohd Sofian (2020)
A review of the extant literature established that the Islamic financial services industry (IFSI) needs to sustain its growth momentum. This is due to the downfall of the world’s largest banks in 2008, which has shaken the global financial industry. Besides, external challenges emerging in the global financial industry have affected the performance of Islamic banks in Malaysia. To overcome such problems, existing reports and several authors have suggested that Islamic banks should get involved in corporate social responsibility (CSR) activities and disclose such activities in the annual reports. It is argued that corporate social responsibility disclosure (CSRD) can increase the business performance of Islamic banks in terms of corporate reputation and financial performance. However, there is an absence of an Islamic CSR framework for Islamic banks in Malaysia. As a critical response to this, this study aimed to establish a modified integrated Islamic CSRD index (MIICSRDi) for Islamic banks in Malaysia. This study also examined whether stakeholders perceived that the MIICSRDi has an influence on the financial performance of Islamic banks in Malaysia. In addition, this study investigated the mediation role of corporate reputation in the relationship between the MIICSRDi and financial performance as perceived by the stakeholders. Particularly, stakeholder theory explains the establishment of the MIICSRDi as well as the perceived relationship between the MIICSRDi and financial performance. This study integrated the stakeholder theory with the Shariah principles (unity, equilibrium, free will, responsibility, and tazkiyah) and the ‘urf principle (customary practice). Furthermore, signalling theory clarifies the mediation role of corporate reputation in the relationship between the MIICSRDi and financial performance as perceived by the stakeholders. This study utilised a cross-sectional survey design to obtain data from 343 respondents comprising 173 employees and 170 customers of Islamic banks. Before conducting the actual study, the items were validated using exploratory factor analysis (EFA). Through the EFA, 11 dimensions for the MIICSRDi were identified, as well as one dimension for financial performance and two dimensions for corporate reputation. By using Partial Least Squares Structural Equation Modelling (PLS-SEM) analysis, this study discovered that the MIICSRDi is a reflective model that influences the financial performance of Islamic banks. Furthermore, both dimensions of corporate reputation, namely management reputation and social reputation, were perceived as partial mediators in the relationship between the MIICSRDi and financial performance. Management reputation was perceived to have a higher partial mediating effect compared to social reputation. The originality of the study lies in its contribution to the development of the MIICSRDi for Islamic banks in Malaysia as a reflective model based on the integration of the stakeholder theory, Shariah principles, and ‘urf principle. The MIICSRDi can serve as a guideline for the disclosure of CSR activities. The MIICSRDi was regarded as an essential tool for management reputation and in enhancing the financial performance of Islamic banks in Malaysia as perceived by the stakeholders.